2002
DOI: 10.1007/s00125-002-0918-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acid composition during pregnancy and lactation in the rat programs growth and glucose metabolism in the offspring

Abstract: Aims/hypothesis. We investigated of the effects of fatty acid composition of the maternal diet on fetal and postnatal growth, morphology of the pancreas and glucose metabolism and muscle hexosamine concentrations in the adult offspring of rats. Methods. High-fat diets enriched with either saturated or unsaturated fatty acids were fed to female adult rats 2 weeks before mating until the end of the weaning period. After weaning, the offspring was maintained on a diet with a balanced fatty acid content. At 3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Furthermore, we found that maternal HFD results in a decreased number of pups delivered that may be due to composition of dietary fatty acids which reportedly affect fertility and induce a higher resorption number (Buckley et al, 2005). It is worth noting that similar findings have been previously reported by Flint and co-workers, in mice, and others in a different species, the rat, further corroborating the critical role played by maternal diet in such time window (Siemelink et al, 2002; Buckley et al, 2005; Flint et al, 2005). In this context, the lack of the p66 Shc gene plays a protective role, at least for selected parameters such as dam mortality and cannibalistic behavior.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, we found that maternal HFD results in a decreased number of pups delivered that may be due to composition of dietary fatty acids which reportedly affect fertility and induce a higher resorption number (Buckley et al, 2005). It is worth noting that similar findings have been previously reported by Flint and co-workers, in mice, and others in a different species, the rat, further corroborating the critical role played by maternal diet in such time window (Siemelink et al, 2002; Buckley et al, 2005; Flint et al, 2005). In this context, the lack of the p66 Shc gene plays a protective role, at least for selected parameters such as dam mortality and cannibalistic behavior.…”
Section: Discussionsupporting
confidence: 84%
“…The effect of fatty acid composition of the maternal diet on fetal and postnatal growth, and pancreas morphology was examined [78]. A HFD rich in unsaturated fat (UFA: menhaden fish oil) was associated with an increase in pancreatic islet numbers.…”
Section: Ratmentioning
confidence: 99%
“…A HFD rich in unsaturated fat (UFA: menhaden fish oil) was associated with an increase in pancreatic islet numbers. A diet rich in saturated fat (SFA: coconut oil) was associated with a reduction in the number of large islets and a faster and more robust insulin response to a glucose load [78]. The programming effect on the pancreas alters the structure and function of islets associated with a predisposition towards glucose intolerance and diabetes.…”
Section: Ratmentioning
confidence: 99%
“…Although sharing the usual suspect of diabetic symptoms, such as hyperglycemia, hyperinsulinemia, overweight, elevated fat content, liver and plasma TG, FFA and leptin levels, GDM is distinct from type 2 diabetes in that GDM also affects reproductive outcome and fetal development (Lawrence et al 1989, Ishizuka et al 1999, Yamashita et al 2001, Siemelink et al 2002, Buckley et al 2005. Results from our study were consistent with reports on the same db/C GDM mouse model, with w10% increase in body weight from litters born by GDM dam, whereas miR-PE transplated GDM females gave birth to litters with body weight comparable to those from WT dam.…”
Section: Discussionmentioning
confidence: 99%
“…One reported adverse effect of GDM is fetal mal-development, in that it worsened reproductive outcome in animal model with less fetuses (Siemelink et al 2002, Buckley et al 2005. Particularly in db/C GDM mouse model, fetus weight at term was reported to increase by 5-8% (Lawrence et al 1989, Yamashita et al 2001.…”
Section: Mir-pe Transplant Improved Reproductive Outcome Of Gdm Femalesmentioning
confidence: 99%